Intramyometrial pregnancy presenting as abnormal uterine bleeding in perimenopausal female - Amrita Razdan Kaul; Usha Priyambada Gupta; Divya Kant; Anita Kant (Wolters Kluwer Medknow Publications, 2022)
Abnormal uterine bleeding (AUB) is frequently encountered in the gynecological complaint of perimenopausal female visiting the outpatient department. Beginning in mid-40s, perimenopause is often marked with menstrual irregularities. Intramyometrial pregnancy (IMP) is a rare type of ectopic pregnancy with an incidence of <1% of all ectopic gestation may present as AUB in perimenopausal female. It remains a diagnostic challenge, especially in background of negative pregnancy test with the lesion ultrasonographically mimicking a fibroid with or without degeneration or an adenomyoma. We report the case of a 41-year-old perimenopausal female presenting with AUB not responding to medical management and ultrasound suggestive of degenerative fibroid. Hence, total laparoscopic hysterectomy was done and histopathology revealed the lesion to be IMP. The aim of this case report is to consider this rare entity as a possible cause of AUB in perimenopausal female even in the pretext of negative pregnancy test.